Blood Flow Restriction Training in Postoperative Musculoskeletal Rehabilitation - Rodziewicz, Bartosz; Fidut, Mateusz; Kacperski, Mikołaj (Journal of Education, Health and Sport, 2026)
Background: Blood flow restriction (BFR) training applies partial vascular occlusion during low-load exercise, offering a clinically compelling adjunct in postoperative rehabilitation. It addresses the paradox of maintaining muscle mass when conventional high-load exercise is contraindicated. Aim: To conduct a narrative review of BFR’s mechanisms, efficacy, and safety in postoperative musculoskeletal disorders, emphasizing ACL reconstruction, total knee arthroplasty (TKA), rotator cuff, and meniscal surgery. Material and Methods: A systematic search of PubMed, Web of Science, and Scopus was performed for English, peer-reviewed human studies published between January 2005 and March 2026. Included studies employed defined BFR protocols for perioperative or postoperative musculoskeletal rehabilitation. Results: Based on 29 studies, BFR significantly mitigates quadriceps atrophy and accelerates strength recovery post-ACL reconstruction compared to load-matched controls. Its efficacy extends to TKA, rotator cuff, and meniscal procedures. Mechanisms include metabolic stress, mTORC1 activation, hormonal upregulation, and regenerative intercellular mitochondrial transfer. BFR is safe when utilizing individualised limb occlusion pressure (LOP) protocols. Conclusions: BFR enables load-compromised patients to achieve resistance training adaptations previously requiring high intensities. Standardising protocols and conducting multicentre trials are priorities for evidence-based integration.